(untitled) (Costos y Gestión, 2022)
The objective of the study is to identify the production costs of shrimp microproducers in the region of Tibau do Sul, in the state of Rio Grande do Norte, as well as to evaluate the economic/operational viability of the activity. The collected data were separated into three groups, according to the annual production volume and the costs were classified as direct and indirect, fixed and variable. The averages of the total costs of production of the shrimp farmers by group, the averages of the cost of shrimp per kilo, billing, operating result, and the average of the contribution margin were calculated. The results show that the highest costs in production are with direct materials. Variable costs are the most representative, with emphasis on labor, feed, and stocking (post-larvae). About fixed costs, maintenance cost was the most relevant. Regarding the cost of shrimp, it was possible to identify that it is influenced by the area of the ponds and the volume of production, with the cost per kilo being higher for producers with low production capacity. It was found that the activity is profitable and viable, even in periods when the sale price is low.